2008
DOI: 10.1021/jp8059807
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hydration on Protein Dynamics: Combining Dielectric and Neutron Scattering Spectroscopy Data

Abstract: Combining dielectric spectroscopy and neutron scattering data for hydrated lysozyme powders, we were able to identify several relaxation processes and follow protein dynamics at different hydration levels over a broad frequency and temperature range. We ascribe the main dielectric process to protein's structural relaxation coupled to hydration water and the slowest dielectric process to a larger scale protein's motions. Both relaxations exhibit a smooth, slightly super-Arrhenius temperature dependence between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

40
248
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(294 citation statements)
references
References 43 publications
(147 reference statements)
40
248
2
Order By: Relevance
“…For example, it has been reported that the transition is coupled to the onset of translational motions in hydration water [47][48][49]. In addition, it has been debated whether the transition is a real phenomenon, or merely a manifestation of the fact that the measurable atomic dynamics enter the experimentally accessible resolution window above certain temperatures [17,18,24,25,27]. In such a scenario, the dynamic motions of the biomolecules may increase without any discontinuity.…”
Section: Resultsmentioning
confidence: 99%
“…For example, it has been reported that the transition is coupled to the onset of translational motions in hydration water [47][48][49]. In addition, it has been debated whether the transition is a real phenomenon, or merely a manifestation of the fact that the measurable atomic dynamics enter the experimentally accessible resolution window above certain temperatures [17,18,24,25,27]. In such a scenario, the dynamic motions of the biomolecules may increase without any discontinuity.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6] But, recently it has been suggested that it may be correlated to anharmonic and glass transitions observed at T D ∼ 180 − 200 K and T g ∼ 80 − 100 K, respectively. As pointed out by Khodadadi et al [7] both have different physical origin and should not be confused.…”
mentioning
confidence: 91%
“…The BP presents similar thermal properties, as described in the literature. [7,20] Thus one could assign the low frequency band in the 20 − 60 cm −1 spectral window to the BP . The temperature dependence of the BP is better accomplished compensating normalizing the spectra by the Bose-Einstein occupation factor.…”
mentioning
confidence: 99%
“…Because we are focusing on the hydration water, we evaluate τ θ by considering the T 1s values and by assuming the constant values a = 1.38Å, b = 0.92Å, and r = 1.52Å [60]. Figure 3 compares the thermal behaviors of τ θ in lysozyme hydration water measured by NMR (h = 0.3), dielectric spectroscopy (h = 0.37) [24], and neutron scattering (h = 0.4) [25], with that of bulk water at ambient pressure [57] and emulsified water at 2 kbar [61]. Note that when the temperature drops below the temperature of irreversible denaturation, the reorientational correlation time in hydration water is slower than in bulk Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although this precise value of temperature has been debated, given the possibility of inadequate instrumental resolutions, there is a consensus that the crossover occurs and that it is important [21][22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%